Effects of Zinc Chloride on Hematological, Biochemical and Histological indicators in Female Climbing Perch (Anabas. testudineus) - Wasan Abdulmunem Taha, Syakirah Samsudin, Shatha Hazem Shakir, and Huda Ayad Hameed (International Journal of Advanced Science and Technology, 2020)
Anabas testudineus or climbing perch is typically known as puyu. The species are important in the East Asian countries among eater (Malaysia, Thailand, India, and China) because of the high content of nutrition materials. The purpose of this study was to evaluate the ZnCl2 on the blood parameters, biochemical indicators, and histological changes in female A. testudineus, after exposure to zinc chloride 2mg/L, for 35 days. The results of this study showed that exposure to ZnCl2 led to a significant decrease (p < 0.05) in the number of red blood cells compared to the control group. The number of white blood cells, blood glucose, liver enzymes Alanine Aminotransferase (ALT), Aspartate Transaminase (AST), and Alkaline Phosphatase (ALP) significantly increased (p < 0.05) compared to the control group. A significant increase (p < 0.05) in the concentration of the Zn was identified in the muscle tissues in the group treated by ZnCl2 compared to the control group. Many histological changes were observed in the tissues sampled from the ovaries, liver, intestine, and gills such as cellular bulging, swelling, and necrosis. The study concluded that exposure of female A.testudineus to heavy metals led to impact significant changes in the blood parameters, biochemical indicators, and histological changes. The data obtained can be used to reduce the impact of heavy metals on fish, by using advanced techniques to treat wastewater and industrial water, before they are released into the water.